Art meets science and spirituality in a changing economy - Wijers, Louvrien; Harris, Maxine; Rochlin, Sheldon (Asset Foundation, 1992)
Drawn from the Conference in Amsterdam in September 1990 and from interviews with participants at their homes and workplaces throughout the world, among the topics discussed at the conference are the groundless nature od reality and of how what we percieve is not just something out there, but is an interdependent relationship between the knower and the known. Includes interviews with Jacques Vanders Heyden spaking of the interconnection between inner and outer reality, Francesco Varela speaking about the Buddhist theory of mind and modern cognitive science and Mother Tessa Bielecki at her monastic retreat in Nova Scotia. Scenes of Tibetan life in India are woven in Varela's speech